Exploring influencing factors in breast cancer survivors’ experience in Lebanon - Saab, Marwa; Han, Xue (Frontiers in Psychology, 2022)
Background: The research objective was to investigate social and cultural factors affecting BCS' experiences in the Lebanese society. Methods: A snowball sampling of 20 breast cancer survivors participated in the study. Semi-structured open-ended interviews were used to collect data. Results: The results showed that family support and religious beliefs were the primary supporting sources for breast cancer survivors. On the other hand, their body image and children were the main concerns. Thus, family and religious beliefs were needed to overcome breast cancer daily burden. Conclusions: Women with breast cancer perceived their cancer experience through their social roles, reflecting a concern of image and role preservation.